Health disparities and equity in the era of COVID-19. Issue 1 (16th March 2021) - Nana-Sinkam, Patrick; Kraschnewski, Jennifer; Sacco, Ralph; Chavez, Jennifer; Fouad, Mona; Gal, Tamas; AuYoung, Mona; Namoos, Asmaa; Winn, Robert; Sheppard, Vanessa; Corbie-Smith, Giselle; Behar-Zusman, Victoria
Abstract: Over the last year, COVID-19 has emerged as a highly transmissible and lethal infection. As we address this global pandemic, its disproportionate impact on Black, Indigenous, and Latinx communities has served to further magnify the health inequities in access and treatment that persist in our communities. These sobering realities should serve as the impetus for reexamination of the root causes of inequities in our health system. An increased commitment to strategic partnerships between academic and nonacademic health systems, industry, local communities, and policy-makers may serve as the foundation. Here, we examine the impact of the recent COVID-19 pandemic on health care inequities and propose a strategic roadmap for integration of clinical and translational research into our understanding of health inequities.